2016
DOI: 10.1108/jd-10-2014-0149
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the information behaviour of users of Welsh Newspapers Online through web log analysis

Abstract: Structured Abstract:Purpose: Webometric techniques have been applied to many websites and online resources, especially since the launch of Google Analytics. To date, though, there has been little consideration of information behaviour in relation to digitised newspaper collections. This paper addresses a perceived gap in the literature by providing an account of user behaviour in the newly launched Welsh Newspapers Online.Design/methodology/approach: The author collected webometric data for Welsh Newspapers On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…This research directly highlights the lack of newspaper use studies within the United States. Gooding noted the gap in recent literature surrounding user information seeking behavior for digitized newspaper collections in his research study, which employed "webometric techniques" to evaluate the use of the then newly launched Welsh Newspapers Online discovery interface (Gooding, 2016). While this method explored web server content logs, this research remains highly relevant to this present study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research directly highlights the lack of newspaper use studies within the United States. Gooding noted the gap in recent literature surrounding user information seeking behavior for digitized newspaper collections in his research study, which employed "webometric techniques" to evaluate the use of the then newly launched Welsh Newspapers Online discovery interface (Gooding, 2016). While this method explored web server content logs, this research remains highly relevant to this present study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though some scholars have pointed to digital technologies altering reading practices, with an increase in the use of e‐texts (Given & Willson, 2018; Sukovic, 2008; Talja & Maula, 2003; Toms & O'Brien, 2008), such findings are less relevant to archives as the most recent data suggests that the majority of physical archival holdings are not digitised (Poll, 2010). Furthermore, Gooding's (2016) study of webometric data from Welsh Newspapers Online also found that users' behaviours in an online environment were more indicative of changes to search than to reading.…”
Section: Related Literaturementioning
confidence: 99%
“…Sfakakis and Kapidakis (2002) distinguished different search patterns for search in various collections -ranging from medical bibliography, and archaeological records, to PhD dissertations -of the Hellenic National Documentation Center in terms of average session length (mostly short sessions with about three interactions) and use of certain search fields, such as any, author, title. More recently, Gooding (2016) showed differences between online and off line search behavior in a Welsh newspaper archive, describing online behavior in terms of number of visits, browsing and viewing content, and time spent on search (about 17 minutes per session and visiting over 20 pages per visit). The data used combine Google analytics with log analysis.…”
Section: Related Workmentioning
confidence: 99%